Neural tube defect among newborns in public hospitals of Tigray region, northern Ethiopia: A cross-sectional study - Goitom Girmay; Berhane Hailu Gebrezgi; Hiwot Gebrewahid; Aman Teklu; Guesh Mebrahtom; Gebrekiros Gebremichael Meles; Ebud Ayele Dagnazgi; Fireweyni Fisshatsion; Birhane Mekonen Negash (PLoS ONE, 2025)
Background Neural tube defects are serious congenital abnormalities caused by abnormal neural tube closure that occur between third and fourth weeks of pregnancy. Globally, neural tube defect is one of the top causes of morbidity and mortality among children under the age of five years. Ethiopia bears the highest adjusted mortality rate attributable to neural tube defects among sub-Saharan African countries. Despite this burden, neural tube defects remain understudied in Tigray, a region recently devastated by conflict. Objective To assess the prevalence and factors associated with neural tube defect among newborns in public hospitals of Tigray, northern Ethiopia, 2024 Methods A facility based cross sectional study design was conducted among 1155 newborns in randomly selected public hospitals in the Tigray region from April 1 to May 30, 2024. Study participants were selected using a systematic random sampling technique. Data were collected through interviewer-administered, pretested, and structured questionnaires. Variables with a p-value of less than 0.25 in the bivariate logistic regression were included in the multivariable analysis to assess their independent effects. Associations between dependent and independent variables were considered statistically significant at a p-value < 0.05. Results The overall prevalence of neural tube defects in this study was 3%. Residence (AOR=3.37, 95% CI: 1.46-7.77), folic acid supplementation before and during pregnancy (AOR=0.14, 95% CI: 0.06-0.33), having no medical illness during pregnancy (AOR=0.10, 95% CI: 0.04-0.21), food consumption score (AOR=2.90, 95% CI: 1.10-7.82), and alcohol consumption during pregnancy (AOR=2.90, 95% CI: 1.30-6.45) were the determinants for neural tube defects. Conclusions The prevalence of neural tube defects is comparatively high among newborns born in Tigray’s public hospitals as compared to previous studies. Residing in rural areas, folic acid supplementation before and during pregnancy, having no medical illnesses during pregnancy, poor food consumption scores, and alcohol consumption during pregnancy were the determinants for neural tube defects. Preventive strategies, such as periconceptional folic acid supplementation, folate fortification, promoting healthy dietary practices, avoiding alcohol consumption, early maternal screening, and treatment of medical illnesses, are essential at both regional and national levels.